THE ROLE OF VIRTUAL REALITY IN COMPUTER ENGINEERING: IMPACTS ON COGNITIVE AND EMOTIONAL PROCESSES - Vikrant Sharma (Bulletin of Engineering Science, Technology and Industry, 2024)
Virtual Reality (VR) technology has emerged as a transformative tool in computer engineering, offering immersive experiences that profoundly influence cognitive and emotional processes. This research explores the multifaceted impacts of VR on human cognition and emotion, examining its applications across various domains such as education, healthcare, and entertainment. By simulating interactive environments, VR enhances spatial awareness, memory retention, and decision-making abilities through realistic simulations and interactive learning experiences. Furthermore, VR's ability to evoke emotions and empathy fosters deeper engagement and emotional resonance in users. This paper reviews empirical studies and theoretical frameworks that elucidate the mechanisms through which VR influences cognitive processes, including attention, perception, and learning, as well as emotional responses such as presence and immersion. Insights gained from this research contribute to understanding VR's potential in enhancing human-computer interaction and shaping future advancements in computer engineering.